KNOWLEDGE LEVEL OF UNDERWEAR PASSING IN VOLLEYBALL OF GRADE VII STUDENTS OF SMP NEGERI 1 SIAK HULU KAMPAR DISTRICT - Yulianti, Mimi (UNIVERSITAS NEGERI JAKARTA POSTGRADUATE OF PHYSICAL EDUCATION DEPARTMENTS, 2025)
This study aims to determine the level of knowledge of volleyball underhand passing of class VII students of SMP Negeri 1 Siak Hulu, Kampar Regency. This type of research is quantitative description with survey planning method and data collection technique using multiple choice test instrument. The subjects in this study were 360 class VII students of SMP Negeri 1 Siak Hulu, Kampar Regency. The sample was taken using purposive sampling technique , so the number of samples in this study was 69 people. The instrument used was a multiple choice test instrument totaling 10 items. The data analysis technique used descriptive analysis which was stated in percentage . Based on the results of data analysis and discussion, it can be concluded that the level of knowledge of volleyball underhand passing of class VII students of SMPN 1 Siak Hulu, Siak Hulu District, Kampar Regency is in the